Change in function of thl - and th2-lymphocytes and cytokine profile at chronic intoxication of ethanol - A.A. Svistunov; P.F. Zabrodsky V.G. Lim; V.A. Grishin (Саратовский научно-медицинский журнал, 2010)
It has been established during the experiments carried on noninbred rats that chronic intoxication of ethanol (30 days, total dose - 6,0 LD50) essentially reduces concentration of cytokines (IFNy, IL-2, IL-4, IL-6,IL-10) in blood, reduces interrelation of IFNy/IL-4 in comparison with the control, suppresses immune reactions, indicating the greater lesion of Th1-cells in comparison with Th2-lymphocytes